Мультикультуралізм як проблема ідеологічного вибору в Україні: конфлікт логіки "модерну" з "постмодерністською" риторикою - Вовк, Д.О.; Вовк, Д. О.; Vovk, D. (My University, 2013)
In article analysis features of the socio-political environment in a modern and postmodern, study the existing conflict in Ukraine between the logic of modern and postmodern rhetoric, identifying trends «multiculturalism» as an element of postmodern logic in Ukraine.
Вовк Д. О. Мультикультуралізм як проблема ідеологічного вибору в Україні: конфлікт логіки "модерну" з "постмодерністською" риторикою / Д. О. Вовк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С.50-58.
Keywords: соціально-політичне ціле в умовах модерну та постмодерну; конфлікт в Україні між логікою модерну та риторикою постмодерну; тенденції розвитку мультикультуралізму як елементу логіки постмодерну в Україні; социально-политическое целое в условиях модерна и постмодерна; конфликт в Украине между логикой модерна и риторикой постмодерна; тенденции развития мультикультурализма как элемента логики постмодерна в Украине; socio-political entity in the conditions of modern and postmodern; conflict in Ukraine between the logic of modern and postmodern rhetoric; development trends of multiculturalism as part of the logic of postmodernism in Ukraine